Metodologi DMAIC untuk Meminimumkan Penolakan Produk Tahu Kuning oleh Agen Distributor - Indrasari, Lolyka Dewi; Ana Komari; Afiff Yudha Tripariyanto; Krishna Tri Sanjaya; Saufik Lutfianto (Journal of Research and Technology, 2021)
This research aims to 1) find out the cause of yellow tofu quality rejection by distributor agents in the supply chain, 2) know the comparison of rejection by the distributor agent pre-implementation and post-implementation of DMAIC methodology, 3) know the decrease in rejection by distributor agents in the supply chain. Research methods use the DMAIC methodology. The DMAIC method as the basis for determining the percentage value decreased rejection of yellow tofu products carried out by the distributor agent. The implementation of this research as an effort to provide the value of minimization of the type of rejection that occurs. This research resulted in 1) the cause of yellow tofu quality rejection by distributor agents in the supply chain is the presence of faded, watery, easily destroyed, bantat, torn 10%, torn 25%, smells sour and less chewy, 2) the comparison of rejection by the distributor agent pre-implementation and post-implementation of DMAIC methodology is 34% compared to 18%, 3) decreased rejection by distributor agents in the supply chain post DMAIC methodology by 16%. The three conclusions of this study are in accordance with the goals achieved. Consistent application of DMAIC methodology may provide more significant declines. The implications of this study compare the pre and post DMAIC methodology in the first, second, and third.